Elaboration of an Imprinted Polymer Film Based on Chitosan Electrodeposition for the Voltammetric Detection of BPA. Issue 2 (7th January 2020) - Chakroun Galai, Hajer; Namour, Philippe; Bonhomme, Anne; Bessueille, François; Besbes Hentati, Salma; Jaffrezic-Renault, Nicole
Abstract : A voltammetric sensor for bisphenol A (BPA) detection was developed. It was based on a gold electrode modified by an electrodeposited molecularly imprinted chitosan (CS) film. Fourier Transformed Infrared spectroscopy, scanning electron microscopy and electrochemistry were used to characterize and compare the surface of the molecularly imprinted polymer (MIP) and non-molecularly imprinted polymer (NIP) films. The analytical performance of this biosensor was then established using square wave voltammetry (SWV) of the ferro/ferricyanide redox probe, in the range of −300 and 600 mV. The oxidation peak current was proportional to the logarithm of BPA concentration in the range between 10 −3 M to 10 −21 M with a limit of detection of 0.67 × 10 −21 M. The elaborated sensor showed good repeatability (RSD 2.08%), reusability and recognition of BPA in the presence of similar structural moieties. The proposed sensors were successfully employed to determine BPA in real plastic bottles for drinking water.